An Assessment of the South African Photovoltaic Sector within the Technological Innovation System Framework - Walwyn, David (University of Pretoria, 2019)
Mini Dissertation (MSc(Master of Engineering in Technology & Innovation Management))--University of Pretoria, 2018.